Impact of Formal Climate Risk Transfer Mechanisms on Risk-Aversion: Empirical Evidence from Rural Ethiopia - Kaelab K. Haile; Eleonora Nillesen; Nyasha Tirivayi (Center for Economic Studies and ifo Institute (CESifo), 2019)
This study examines the effect of smallholder farmers' access to a formal climate risk transfer mechanism on their risk preferences. Survey and experimental data were collected from smallholder farmers that have access to weather index-based crop insurance (WICI) in Ethiopia. We use an endogenous switching (ESP) model to address self-selection and simultaneity bias. Results from the ESP model show that farmers who purchased WICI are less likely to be risk-averse compared with non-purchaser farmers. Similarly, non-purchasers would have attained a significant reduction in their risk-aversion if they had taken up the insurance product. We also find that WICI has a positive and statistically significant effect on farmers' real-life risk-taking behavior as exemplified by mineral fertilizer use. The implication of our findings is that formal climate risk transfer mechanisms can positively influence households' economic decisions and outcomes, through reducing risk aversion. Therefore, they can possibly contribute to poverty alleviation and economic development within agrarian economies that are exposed to recurrent and severe climate shocks.
Keywords: C91; D03; I38; N27; 330; weather index-based crop insurance; endogenous preferences; experimental risk elicitation; endogenous switching probit; sub-Saharan; Ethiopia